The Influence of Assets, Credit Guarantees, and Interest Rates on Customer Credit Decisions - Cherly Elisabeth (Golden Ratio of Taxation Studies, 2023)
This research was conducted to analyze Assets, Credit Guarantees, and Interest Rates on Customer Credit Decisions at Bank SULSLBAR Majene Branch. This study uses a type of quantitative research, quantitative methods are all data expressed in the form of numbers. Data collection was carried out through a questionnaire with a quantitative approach. The sampling technique in this study was simple random sampling with a total of 100 respondents and using multiple regression analysis. The results of the study show that partially assets have a positive and significant effect on customer credit decisions, as evidenced by the t count value which is greater than t table, namely 2.337 > 1.984 and a significance level smaller than 0.05, namely 0.021. The credit guarantee variable partially also has a positive and significant effect on customer credit decisions, as evidenced by the t-value which is greater than t-table, namely 1.999>1.984 and a significance level that is less than 0.05, namely 0.048. The interest rate variable partially has a positive and significant effect on customer credit decisions, as evidenced by the t-value which is greater than t-table, namely 3.648 > 1.984 and a significance level that is smaller than 0.05, namely 0.000. Assets, credit guarantees, and interest rates simultaneously have a positive and significant effect on customer credit decisions, as evidenced by the calculated f value, which is greater than f table, namely 37.074 > 2.92.